The Complex Role of Mental Time Travel in Depressive and Anxiety Disorders: An Ensemble Perspective - Kellogg, Ronald T.; Chirino, Cristina A.; Gfeller, Jeffrey D. (Frontiers in Psychology, 2020)
The ensemble hypothesis proposes that uniquely human cognitive abilities depend on more than just language. Besides overt language, inner speech and causal interpretations, executive attention, mental time travel, and theory of mind abilities are essential parts that combine additively and even multiplicatively. In this review, we consider the implications of the ensemble hypothesis for the psychopathologies of anxiety and depression. Generalized Anxiety Disorder and Major Depressive Disorder are two of the most common mental disorders worldwide. The mechanisms that differentiate them are difficult to identify, however. Mental time travel has been implicated in models of depressive and anxiety disorders but here we argue that two other ensemble components, namely, interpreter biases and executive attention, must also be considered. Depressive and anxiety disorders have both been found to show impairments in all three of these components, but the precise relationships seem to distinguish the two kinds of disorders. In reviewing the literature, we develop models for depression and anxiety that take into account an ensemble of mental components that are unique for each disorder. We specify how the relations among mental time travel, interpreter biases, and executive attentional control differ in depression and anxiety. We conclude by considering the implications of these models for treating and conceptualizing anxiety and depression.